Pengembangan Media Buku Operasi Hitung Berbasis Montessori dalam Meningkatkan Pemahaman Matematika Dasar Kelas B pada Siswa KB Aisyah Rahman - Anggraini, Hesti Dwi; Hasanah, Hisbiyatul; Zahro, Ianatuz (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to develop a Montessori-based arithmetic operation book media to improve basic mathematical understanding in early childhood, especially grade B students at Aisyah Rahman Kindergarten. The background of this study is the low basic arithmetic ability of children caused by the use of conventional learning media such as worksheets and whiteboards that are less suitable for the learning characteristics of early childhood. Children at this stage learn through concrete activities, play, and manipulatives, so learning media that can facilitate these needs are needed. The research method used is the ADDIE development model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study was conducted at Aisyah Rahman Kindergarten with 25 students in group B as research subjects. Data collection was carried out through observation, interviews, documentation, and tests of understanding basic mathematical concepts (pretest and posttest). The results of the study showed that the Montessori-based arithmetic operation book media developed was assessed as very feasible in terms of content, design, and usability by experts. The implementation of media in learning showed a significant increase in students' mathematical comprehension scores, with an average pretest score of 54.2 and an increase to 84.8 in the posttest. This media encourages students' active involvement in learning and facilitates them in understanding mathematical concepts concretely through a discovery learning approach. Thus, this Montessori-based arithmetic operations book media is effective as an alternative learning medium to improve basic mathematical skills in early childhood and is in line with the characteristics of their cognitive development.